Serotonin transporter (5-HTT) and gamma-aminobutyric acid receptor subunit beta3 (GABRB3) gene polymorphisms are not associated with autism in the IMGSA families. The International Molecular Genetic Study of Autism Consortium. - Maestrini, E; Lai, C; Marlow, A; Matthews, N; Wallace, S; Bailey, A; Cook, E; Weeks, D; Monaco, A (1999)
Previous studies have suggested that the serotonin transporter (5-HTT) gene and the gamma-aminobutyric acid receptor subunit beta3 (GABRB3) gene, or other genes in the 15q11-q13 region, are possibly involved in susceptibility to autism. To test this hypothesis we performed an association study on the collection of families from the International Molecular Genetic Study of Autism (IMGSA) Consortium, using the transmission disequilibrium test. Two polymorphisms in the 5-HTT gene (a functional insertion-deletion polymorphism in the promoter and a variable number tandem repeat in the second intron) were examined in 90 families comprising 174 affected individuals. Furthermore, seven microsatellite markers spanning the 15q11-q13 region were studied in 94 families with 182 affected individuals. No significant evidence of association or linkage was found at any of the markers tested, indicating that the 5-HTT and the GABRB3 genes are unlikely to play a major role in the aetiology of autism in our family data set.